O18 TREATMENT OF ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY (TENTACLE STUDY). (23rd November 2019) - van Workum, Frans; Verstegen, Moniek; Klarenbeek, Bastiaan; Siersema, Peter; Schouten, Jeroen; Hannink, Gerjon; van Berge Henegouwen, Mark; Daams, Freek; Polat, Fatih; Willem Haveman, Jan; Heisterkamp, Joos; Nieuwenhuijzen, Grard; et al.
Abstract: Aim: The aim of this study is to investigate which factors contribute to anastomotic leakage severity and to compose an evidence based anastomotic leakage severity score. Secondly, we aim to investigate which anastomotic leakage characteristics are associated with success of different anastomotic leakage treatments and to compare the effectiveness of different initial anastomotic leakage treatments for anastomotic leakage classified according to severity and leakage characteristics. Background: Anastomotic leakage occurs in 0%-30% after esophagectomy for cancer. It is a severe complication with mortality rates approximately ranging from 2%-12%. In addition, it is associated with a prolonged ICU treatment and hospital stay. Anastomotic leakage severity is currently graded according to how it is treated (grade I: conservative treatment, grade II: endoscopic/radiologic intervention and grade III: surgical intervention). However, this scoring system cannot be used to guide decision making when anastomotic leakage is diagnosed in a clinical setting. Factors that may influence the severity of the anastomotic leakage are (amongst others) location of the anastomosis, estimated surface of the defect, estimated circumference of the defect, extent of contamination, degree of sepsis and time from diagnosis until therapy. However, little is known about to what extent these and other factors contribute to anastomotic leakage severity. In addition, there is a paucity of data on what leakage characteristics dictate the success of a specific treatment. Methods: We will perform an international multicenter retrospective cohort study. All adult patients with anastomotic leakage according to the ECCG definition after esophagectomy and gastric conduit reconstruction for esophageal cancer are suitable for inclusion. We aim to include at least 1000 patients. The primary outcome parameter is 90-day mortality. Secondary outcome parameters are in-hospital mortality, 30-day mortality, 180-day mortality, comprehensive complications index, total number of reinterventions, hospital and ICU length of stay and hospital related costs. Results: Data collection will take place from April 2019 until December 2019. Study results are expected in June 2020. Conclusion: We hypothesize that we will be able to identify factors that influence the severity of the anastomotic leakage and to compose a leakage severity score. Furthermore, we expect to identify leakage characteristics dictating the success of a specific treatment.